Comparison of 3D ultrasound, 2D ultrasound and 3D Doppler in the diagnosis of endometrial carcinoma in patients with uterine bleeding: A systematic review and meta-analysis. (October 2022) - Xydias, Emmanouil M.; Kalantzi, Sofia; Tsakos, Elias; Ntanika, Anna; Beis, Nikolaos; Prior, Matthew; Daponte, Alexandros; Ziogas, Apostolos C.
Highlights: 3D ultrasound modalities could facilitate endometrial cancer diagnosis. Endometrial volume was more specific than endometrial thickness. 3D Doppler indices were more sensitive than endometrial volume. 3D modalities additionally offer other technical and practical benefits. More research is required to further investigate 3D diagnostic efficacy. Abstract: Endometrial cancer is a common malignancy affecting women worldwide. Usually, it clinically manifests with uterine bleeding, although identical clinical manifestations occur in benign conditions as well, with several endometrial biopsies being conducted unnecessarily. Therefore, an accurate, non-invasive diagnostic test is needed for first-line assessment, so as unnecessary biopsies are limited as much as possible. This systematic review aims to assess the diagnostic accuracy of three-dimensional ultrasound, a relatively novel method in gynecologic assessment, compared to two-dimensional ultrasound and three-dimensional Doppler in the prediction of uterine malignancy in women with abnormal uterine bleeding. The accuracy of endometrial volume, as a diagnostic parameter assessed by three-dimensional ultrasound is compared to diagnostic parameters from the other two methods, namely endometrial thickness and 3D Doppler indices (vascularization index, flow index and vascularization flow index). Articles relevant to our research question were systematically sought in the Web of Science, Scopus and MEDLINE/PubMed databases and underwent rigorous evaluation for inclusion according to the PRISMA 2020 guidelines. Eligible studies were thoroughly assessed for risk of bias and relevant data was extracted and analyzed. Studies were heterogenous and extracted data varied from study to study. Data on endometrial volume was compared to other diagnostic parameters. Forest plots with pooled percentages and hierarchical summary receiver operating characteristic curves were constructed for each comparison. Relative sensitivity and specificity ratios were calculated for each comparison to test for statistical significance. Endometrial volume and thickness comparison showed sensitivity 83% for both parameters and specificity 75% and 69% respectively, with volume being more specific than thickness (p < 0.05). Endometrial volume and Doppler indices comparison showed that sensitivity was 73%, 82%, 81% and 82%, while specificity was 72%, 76%, 75% and 76% for endometrial volume, vascularization index, flow index and vascularization-flow index respectively. All three Doppler indices were significantly more sensitive in the diagnosis of malignancy compared to endometrial volume (p < 0.05) While endometrial thickness remains a reliable predictor of uterine malignancy, endometrial volume appears promising as a method with higher specificity and more reliable measurements. Similarly, vascular indices seem as competent and even more sensitive than endometrial volume as predictors, with the added advantage of semi-automated and reproducible measurements that reflect the whole organ. More comparative studies with standardized protocols should be established, so as reliable cut-off values can be determined and thus standardize and streamline the diagnostic algorithm via the implementation of the three-dimensional modalities in the settings that they are available.